Design and motion control of spherical robot with built-in four-wheel omnidirectional mobile platform - Bu, Suwan (2023)
The objective of this article is to propose a novel spherical robot with a built-in four-wheel omnidirectional mobile platform. The employment of a four-wheel structure helps to improve the friction coefficient and thus reduce the slipping motion. In addition, it increases the velocity augmentation factor, and thus compensation methods can be effectively implemented into the system to decrease the slipping motion further. Moreover, the traction force is increased and thus the loading capacity can be improved correspondingly. First, the schematic structure along with the operating principle of the proposed spherical robot is introduced. Then, the kinematic and dynamic models are formulated analytically. The slipping error between the omnidirectional wheels and the inner wall of the sphere is analyzed. The slip observer and the motion controller are designed, and their convergence is proved theoretically. Subsequently, simulation is conducted to validate the proposed slip observer that is in turn implemented into the motion controller. The trajectory tracking of the spherical robot on a straight line and circle is verified. Following that, one research prototype of the spherical robot with a built-in four-wheel omnidirectional mobile platform is developed. Experimental investigation shows that the research prototype embedded with the slip observer can achieve the trajectory tracking performance very well.